2018
DOI: 10.1097/md.0000000000010587
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral tranexamic acid in total knee arthroplasty

Abstract: Our meta-analysis suggested that the administration of oral TXA provided significantly better results with respect to Hb drop, Hct drop, and drain output without increasing the transfusion rate and the risk of thromboembolic complications after TKA. Nevertheless, our current study with some limitations such as the small sample size only provided limited quality of evidence, confirmation from further meta-analysis with large-scale, well-designed RCTs is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
(72 reference statements)
3
24
0
Order By: Relevance
“…Previously, orthopaedic surgeons were hesitant to adopt TXA into practice because of poorly supported links to venous thromboembolic events, acute renal failure, and stroke. Contraindications to TXA use has been a topic of much debate, and large-scale database studies have found no increased complication risk when TXA was administered to patients with relative contraindications [59][60][61][62]. Despite a comparatively small sample size, our study substantiated prior findings as it showed no increase in overall complication rate with TXA use.…”
Section: Discussionsupporting
confidence: 84%
“…Previously, orthopaedic surgeons were hesitant to adopt TXA into practice because of poorly supported links to venous thromboembolic events, acute renal failure, and stroke. Contraindications to TXA use has been a topic of much debate, and large-scale database studies have found no increased complication risk when TXA was administered to patients with relative contraindications [59][60][61][62]. Despite a comparatively small sample size, our study substantiated prior findings as it showed no increase in overall complication rate with TXA use.…”
Section: Discussionsupporting
confidence: 84%
“…A recent clinical trial compared the use of topical and intravenous tranexamic and aminocaproic acid versus placebo, and the results of the studies investigating the use of oral TXA in joint replacement surgeries 42 were very similar to our study results. 43 To our knowledge, no previous studies have examined oral aminocaproic acid; however, we acknowledge that the variations in methodology, application techniques, different doses of TXA and ε-ACA and different methods to calculate blood loss account for the heterogeneity among studies, making it difficult to compare their results. In the present climate of tightening health care budgets and debate surrounding fiscal austerity, the implications of increasing demand for TKA have led to intense discussion regarding the cost-effectiveness of a new method of antifibrinolytic administration.…”
Section: Discussionmentioning
confidence: 99%
“…30 Although concerns regarding possible thromboembolic risk with tranexamic acid therapy have been expressed, recent systematic reviews have failed to demonstrate any significant increased risk. [32][33][34] DDAVP is a synthetic analog of vasopressin that stimulates endothelial cell secretion of stored VWF into the plasma. 35 Consequently, DDAVP can be used to transiently increase plasma VWF levels in some patients with VWD.…”
Section: Treatment Options For Patients With Low Vwfmentioning
confidence: 99%